The Role of Concentration and Flexibility in Enhancing Topspin Stroke Accuracy among Table Tennis Players - Jeki Haryanto; Friski Amra; Naluri Denay; Eri Barlian; Masrun; Gusri; Yendrizal; Mert Isbilir (Journal of Sport Science and Education, 2025)
Topspin stroke accuracy is a critical determinant of performance in table tennis, as it enables players to control ball placement and gain tactical advantages during competition. Although previous studies have identified the importance of cognitive and physical factors in sport performance, limited research has simultaneously examined the contributions of concentration and flexibility to topspin stroke accuracy. Therefore, this study aimed to investigate the relationships between concentration, flexibility, and topspin stroke accuracy among table tennis players. A cross-sectional correlational design was employed involving 62 table tennis players aged 20–23 years. Concentration was assessed using the Concentration Grid Test, flexibility using the Sit-and-Reach Test, and topspin accuracy using a standardized topspin accuracy test. Data were analyzed using Pearson correlation. The results revealed significant positive correlations between topspin accuracy and concentration (r=0.774, p<0.001) as well as flexibility (r=0.604, p<0.001). In conclusion, concentration and flexibility were significantly associated with topspin stroke accuracy, with concentration showing the strongest relationship. These findings suggest that both psychological and physical factors should be considered in training programs aimed at improving topspin performance in table tennis players.